ANALISIS SISTEM DAN KINERJA PELABUHAN PERIKANAN SEBAGAI PUSAT EKONOMI DI ACEH - Azwar Thaib (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2026)
Fishing ports play a strategic role in supporting fisheries logistics systems, fish distribution networks, and the economic development of coastal communities. However, the fisheries port system in Aceh still faces several challenges, including infrastructure inequality, weak logistics connectivity, and limited functional integration among ports. This study aimed to analyze fisheries port systems and performance as economic centers in Aceh through case studies of PPS Kutaraja, PPN Idi, and PPP Labuhan Haji. The study employed a comparative multi-case study approach using descriptive-comparative and system analysis methods. The results showed that PPS Kutaraja functioned as the main regional fisheries logistics center, PPN Idi served as a regional distribution connector, while PPP Labuhan Haji acted as a local economic base for coastal fishing communities. Although the port hierarchy had been administratively established, logistics and distribution integration among ports had not operated effectively. This study proposed the concept of Bottom-Heavy Fisheries Port System as an approach for strengthening fisheries-based coastal economies in Aceh.